CROSSING OVER IMMUNOELECTROPHORESIS APPLIED TO THE STUDY OF IMMUNOLOGY OF SOUTH AMERICAN BLASTOMYCOSIS - PREVIOUS NOTE - Barbosa, William; Blau, Edith; Mendonça, Joana Rosa; de Oliveira, Raquel Lopes (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
Crossing over ímmunoelectrophoresis was used for detection of antibodies of P. brasiliensis in 31 patients with several clinicai forms of South American blastomycosis. Positive results were obtaíned in 24 of tbese cases. (77,4% positivity). Furthermore it was observed that precipitins were not detected in ali serial serum specimens investigated and that its presence or absence could not be correlated with the period of the disease, treatment or clinicai evolution. Further studies are necessary to as&ess the value of the method in lhe study of this disease.